Cognitive impairment in heart failure patients - Leto, Laura (J Geriatr Cardiol, 2014)
Cognitive damage in heart failure (HF) involves different domains thus interfering with the ability for single patient to self-care and to cope with treatment regimens, modifying symptoms and health behaviours. Many cerebral and functional changes were detected in brain imaging, involving areas of both grey and white matter deputed to cognition. Although various instruments are available to explore cognition, no consensus was obtained on better tools to be used in HF population. Reduction in cerebral blood flow, decreased cardiac output, alterations of cerebrovascular reactivity and modification of blood pressure levels are the main features involved in the etiopathogenetic mechanisms of cognitive deficit. Several cardiac variables, laboratory parameters, demographic and clinical elements were studied for their possible relation with cognition and should be properly evaluated to define patients at increased risk of impairment. The present review gathers available data pointing out assured information and discussing possible areas of research development.